Male-Biased Social Deficits in Chd8+/R2219* Mouse Model of Autism Linked to Hippocampal Abnormalities - Qian Zhang; Yang Qiao; Huixian Li; Jiali Zeng; Jingwen Chen; Hui Zhou; Yuzheng Hu; Jianhong Luo (Neuroscience Bulletin, 2026)
Autism spectrum disorder (ASD) is a neurodevelopmental condition with a 4:1 male bias, yet the biological basis for this sex difference remains poorly understood. Heterozygous mutations in the chromatin remodeler CHD8 confer high risk for ASD, with phenotypes influenced by sex and genetic background. Here, we generated Chd8 +/R2219* mice carrying a CRISPR-Cas9-generated mutation orthologous to a human variant. These mice recapitulated core ASD features, including macrocephaly and autistic-like behaviors. Notably, social deficits showed a male preponderance, directly mirroring the human sex bias. Structural magnetic resonance imaging (MRI) confirmed whole-brain enlargement in mutants, with voxel-based morphometry identifying bilateral hippocampal expansion. Crucially, hippocampal volume correlated with social deficit severity exclusively in male mutants. Functional connectivity analyses revealed disrupted hippocampal networks, and connectivity patterns within socially relevant circuits predicted behavioral outcomes. Together, our findings establish this model as exhibiting pronounced sexual dimorphism and implicate aberrant hippocampal structure and connectivity as key neural correlates of male-biased social deficits.